Synergic interactions between polyphenols and gut microbiota in mitigating inflammatory bowel diseases. Issue 6 (3rd June 2020) - Li, Hao; Christman, Lindsey M.; Li, Ruiqi; Gu, Liwei
Abstract : Polyphenols and gut microbiota act separately and synergistically to alleviate inflammatory bowel diseases. Abstract : Inflammatory bowel diseases (IBD) are a group of chronic and recurring inflammatory conditions in the colon and intestine. Their etiology is not fully understood but involves the combination of gut dysbiosis, genetics, immune functions, and environmental factors including diet. Polyphenols from plant-based food synergistically interact with gut microbiota to suppress inflammation and alleviate symptoms of IBD. Polyphenols increase the diversity of gut microbiota, improve the relative abundance of beneficial bacteria, and inhibit the pathogenic species. Polyphenols not absorbed in the small intestine are catabolized in the colon by microbiota into microbial metabolites, many of which have higher anti-inflammatory activity and bioavailability than their precursors. The polyphenols and their microbial metabolites alleviate IBD through reduction of oxidative stress, inhibition of inflammatory cytokines secretion (TNF-α, IL-6, IL-8, and IL-1β), suppression of NF-κB, upregulation of Nrf2, gut barrier protection, and modulation of immune function. Future studies are needed to discover unknown microbial metabolites of polyphenols and correlate specific gut microbes with microbial metabolites and IBD mitigating activity. A better knowledge of the synergistic interactions between polyphenols and gut microbiota will help to devise more effective prevention strategies for IBD. This review focuses on the role of polyphenols, gut microbiota and their synergistic interactions on the alleviation of IBD as well as current trends and future directions of IBD management.